Trilogy of the body in space: influences of climbing practice on scenic creation in dance - Millás, Cláudia Regina Garcia (2020)
This article presents the description and analysis of three authorial dance works that can be seen as a trilogy of approaching the body in space from the use of a wall on stage, with the practice of climbing as the main source of inspiration and propelling element for scenic creation. The vertical space is investigated as a factor of a(fe)tivation, for mobilizing and affecting both the artist on stage and the audience watching the work. It is observed that the space in question allows the practitioner to enter an unusual place and experience the flow, which requires bodily engagement and integrity, sharpening sensitivity and enabling other ways of seeing and living the world. In this way, the analyzed proposals sought to create other points of view, generating strangeness in the look, so that one could see with more attention, having different readings of the creations presented.